Pelindungan Hak Konstitusional Perempuan Dalam Pencalonan Legislatif Pemilihan Umum Tahun 2024 di Gorontalo - Nasef, Muhammad Imam; Wardhana, Allan Fatchan Gani; Huda, Ni'matul (Universitas Islam Indonesia, 2026)
One of the evaluations of the implementation of the 2024 Election in Indonesia is related to the fulfillment of the 30 percent quota for women in legislative nominations. In the 2024 Election, in the Gorontalo Electoral District, political parties that did not meet the 30 percent quota for women as legislative candidates were allowed to participate in the legislative election. Then, the Constitutional Court corrected and annulled the election results through a Revote in Electoral District 6 Gorontalo because many political parties did not meet the requirements. This decision is certainly interesting to study because it can have a major impact on legislative nominations that must include at least a 30 percent quota for women not only in Gorontalo but applies to all electoral districts in Indonesia. This study examines two things, first, the ratio legis and the urgency of the need to protect women's constitutional rights in legislative nominations in the General Election, second regarding the implications of Constitutional Court Decision Number 125-01-08-29 / PHPU.DPR-DPRD-XXII / 2024 concerning the protection of women in legislative nominations in the upcoming General Election. The research method used is normative juridical with case and statute approach. Secondary research data sources include Constitutional Court Decisions and laws and regulations related to legislative nominations in elections. This study concludes, first, that the Constitutional Court provides guarantees and protection for women in nominating legislative members in the 2024 Election. The 30 percent quota for women in legislative nominations by political parties is an absolute prerequisite for holding legislative elections at all levels. Second, the legal implications of Constitutional Court Decision Number 125-01-08-29 / PHPU.DPR-DPRD-XXII / 2024 require every political party to include a 30 percent quota in nominating legislative members in the Election. If this is not met, the political party cannot participate in the election.